Tax Planning and Firm Size as Determinants of Earnings Management (Evidence from Indonesia's Food and Beverage Sector) - Muhammad Nandiko; Hartono Hartono (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2025)
This study explores the influence of tax planning and firm size on earnings management among food and beverage companies listed on the Indonesia Stock Exchange. The research adopts a quantitative approach, utilizing panel data obtained from annual financial reports. Tax planning is measured using the tax retention rate, while firm size is assessed through the natural logarithm of total assets. Earnings management is analyzed using changes in earnings relative to market value. The sample is selected through purposive sampling with specific inclusion criteria. The analysis employs a panel data regression model, with the random effect model determined as the most appropriate. The findings reveal that both tax planning and firm size have a significant effect on earnings management, both individually and simultaneously. These results suggest that larger firms with efficient tax strategies are more inclined to engage in earnings management practices to maintain financial performance stability.